NATO’s partnership policy: From the military alliance to the security community, and back again - I. L. Prokhorenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Despite the fact that NATO is celebrating its 75th anniversary this year, there is an ongoing debate on the essence and nature of the alliance, its role in international relations in general and the architecture of European security in particular. These discussions are especially relevant now as the system of international relations has entered a period of global transformation. The fact that the alliance has undergone numerous organizational and identity changes throughout its long history makes the problem of understanding the phenomenon of NATO all the more difficult. In order to address this challenge, the article focuses on the key features of NATO’s partnership policy in the post-bipolar world. The author concludes that in the wake of the Cold War, NATO faced a profound identity crisis and set a course for a radical functional expansion, in particular within the framework of partnership policy, by including the issues of post-conflict reconstruction, human and gender security, public diplomacy, climate change, etc. into its agenda. All this seemed to indicate a radical shift of NATO from a traditional military-political association towards a genuine ‘security community’. However, the conflict in Ukraine and the deep impasse between Russia and the West, largely provoked by the NATO’s partnership and enlargement policy, has again brought to the forefront of the bloc’s collective identity-building the traditional binary ‘friend-and-foe’ logic and, especially, self-representation as a military alliance.